グリーンランド氷床の標高2500m表面における昇華 - 佐藤, 和秀; 平林, 幹啓; 東, 久美子; J.P., Steffensen; Kazuhide, Satow; Motohiro, Hirabayashi; Kumiko, Goto-Azuma (2013)
Meteorological and glaciological observations were carried out from June to August, 2012, at NEEM Camp (77°27'N, 51°3.6'W, 2500m a.s.l.) of the Greenland Ice Sheet. Although the temperature in this period was -18 ℃ to nearly 0 ℃ in general, it also often became plus temperature from the middle of July to August, and the very rare rainbows were seen at this area on July 28 and 30. Snowfall, condensation frost and snow melting phenomenon were observed on the ice sheet surface. Measurement of the amount of surface sublimation was performed as follows. The atmometer of the plastic laboratory dish of inside diameter 8.4cm and depth 1.8 cm filled with frozen water, was placed on the table of 1m height from the snow surface, and the weight of this dish was measured at time 9:00 and 21:00 every day, and the amount of sublimation was computed from the weight difference. The amount of daily sublimation (mg/cm2・day) is shown in Figure 1. The amount of sublimation of about 70 to 190 mg/cm2・day is shown, and this is close to the peak values of the amount of daily sublimation obtained on the Mizuho Station of the Antarctic ice sheet (Fujii, 1979). Moreover, there are more amounts of sublimation from time 9:00 to 21:00 than the amounts of sublimation from 21:00 of the previous day to 9:00. 第4回極域科学シンポジウム 個別セッション：[OM] 気水圏 11月15日（金） 国立極地研究所 ３階ラウンジ conference object